(untitled) (World Economics and Finance Bulletin, 2024)
In this article, there is a preferential loan for small businesses and private entrepreneurs state gross domestic product at the expense of funds production of import-substituting export-oriented products when recording indicators. The output is also more profitable, and all new jobs are new businesses. It is highlighted that banks play an extremely large role.